Motivasi Santri Terhadap Pendidikan Formal (MTs) dan Non Formal (Diniyah) di Pondok Pesantren Al-Qur’an Nurul Huda Kecamatan Prajurit Kulon Kota Mojokerto - Noer Faidah; Abdul Jalil; Nur Hasan (VICRATINA, 2019)
This study aims to determine the motivation of santri towards Formal (MTs) and Non-formal (Diniyah) education at the Al-Qur'an Nurul Huda Islamic Boarding School in the Warrior District of Mojokerto. Focus studied are 1) Learning system 2) Learning method 3) Motivation of santri towards formal learning spirit (MTs) and non-formal (diniyah) at Al-Qur'an Nurul Huda Islamic Boarding School in Prrior Kulon District, Mojokerto City. In this study, the research method used was a qualitative method and the type of research used was a case study. The approach used in this study is observation, in-depth interviews, and documentation. Data analysis techniques are by data reduction, data presentation and verification / conclusion drawing. Checking the validity of the data using an extension of participation, persistence / permanence of observation and triangulation. The results of this study, 1) the system used is the salafiyah system (classical), modern (non-classical), for the santri who memorize the Al-Qur'an is done when after reciting the dawn with the Kyai. The system deposits memorization and recalls memorization. 2) methods used in sorogan, badhongan / wetonan, lectures, discussions and for those who memorize the Qur'an using the method of declaration. 3) the motivation possessed by the santri in carrying out formal education (MTs) and Non-formal (Diniyah) which is where they always get an approach in the form of lectures so that their motivations remain and also the ideals they have make as much learning. The provision of adequate infrastructure makes them enthusiastic about learning.